Small Enterprise Challenges and Responses to the COVID-19 Crisis - Saptarshi Dhar; Tahira Farzana (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study proposes a framework combining crisis challenges and response actions for crisis survival of small enterprises during the COVID-19 pandemic in Bangladesh. Design/methodology/approach: We adopted a qualitative research design using a multiple case study method collecting data from four small firms in Bangladesh. Findings: The findings of this study are expected to contribute to the literature on the small enterprise and COVID-19 context, providing useful insight into crisis survival for small firms, especially in developing countries. Research limitations/implications: To counter these challenges, firms adopted short-term and long-term response strategies that resulted in survival for these businesses. Practical implications: We derive a conceptual framework for crisis survival based on the learnings from the cases that would enable small firms to build resilience to crisis episodes. Additionally, we suggest recommendations that small enterprise owners and policymakers can adopt to improve the resilience during exogenous crisis periods. Originality/value: This paper is original Paper type: Research paper